Neutrophil–Lymphocyte Ratio as a Prognostic Marker in Adrenocortical Carcinoma. (3rd April 2021) - Solak, Mirsala; Kraljević, Ivana; Zibar Tomšić, Karin; Kaštelan, Marko; Kakarigi, Luka; Kaštelan, Darko; ,
ABSTRACT: Purpose: The purpose of the present study was to analyze the impact of the neutrophil–lymphocyte ratio (NLR) on the long-term outcomes of patients with adrenocortical carcinoma (ACC). Methods: This retrospective, single-institution study included 48 patients with the diagnosis of ACC. The primary outcomes of the study were differences in overall survival (OS) and disease-specific survival (DSS) with respect to the NLR level. Results: Patients with ENSAT stage IV had higher levels of NLR compared to those with ENSAT stage I–III (5.7 (1.6–12.5) vs 3.3 (1.3–11); p = .01). A higher NLR was also observed among patients with cortisol-secreting tumors (4.6 (1.7–12.5) vs 2.8 (1.3–10.3); p = .003) and those with Ki-67 index >10% (4.3 (1.3–12.5) vs 2.6 (1.6–11.0); p = .005). With respect to survival, the univariate analysis revealed worse ACC-related survival ( p = .02) and OS ( p = .004) in patients with NLR >3.9 than in those with NLR ≤3.9. In addition, patients with NLR >3.9 had a higher Weiss score ( p = .046), a higher Ki-67 index ( p = .006) and a higher disease stage ( p = .01) compared to patients with NLR ≤3.9. No differences between the groups were observed regarding excess glucocorticoid secretion. Conclusion: The study demonstrated that a higher NLR level in ACC patients was associated with unfavorable outcomes in terms of DSS and OS. These results indicate that NLR might be used as an additional marker in ACC risk stratification and identification of patients with the most adverse prognosis.